Management of myelofibrosis: a survey of current practice in the United Kingdom. Issue 12 (3rd September 2012) - Qureshi, Moosa Rashid; MacLean, Cathy; McMullin, Mary Frances; Harrison, Claire
Abstract : Aims: To investigate the experience of clinicians in the management of patients with myelofibrosis, current treatment options and their utility. Methods: We used an internet-based survey Results: Of 105 respondents (mostly consultants), 79% identified bothersome symptoms as the most common issue to be addressed, while for 19%, lack of efficacy of treatment fell into this category. The survey found that a wide variety of treatments are employed but with poor perceived efficacy. Conclusions: This is the first UK based assessment of management of myelofibrosis. Perspectives may evolve with the inception of novel therapeutics in this field, but clinical guidelines for effective management currently recommend a wide variety of agents and suggest a limited likely success rate.